Perancangan Antarmuka Pengguna Sistem Informasi Buku Kejar Prestasi di SMK Negeri 2 Singosari menggunakan Metode Human-Centered Design - Rida Erlangga; Satrio Hadi Wijoyo; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Code of conduct is a series of rules that must be obeyed in a situation. A good education is a must in order to teach good manners. Vocationan High School of State 2 Singosari uses a Kejar Prestasi Book as a tool to encourage their students to do good deeds and also avoid doing things that break the rules. However, There is an obstacle on data collection regarding the Kejar Prestasi Book. Therefore, Vocational High School of State 2 Singosari is planning on creating a system which is able to accommodate the data collection of the students. The good user interface is needed for accommodating its user need. The method which is used for designing the user interface is Human-Centered Design (HCD). Based on the HCD Approach, there are three groups of user and stakeholder which is Vice Principal of Student Affair, Homeroom Teacher, and the Student. Testing the result of the design uses System Usability Scale (SUS) which able to test the usability aspect. Based on the testing, the user interface design for Kejar Prestasi Book, the score result is 76.2 Which is a â€œGOODâ€ category and acceptable by users.